Improved Performances of a Fluidized Bed Photoreactor by a Microscale Illumination System. (24th November 2009) - Ciambelli, Paolo; Sannino, Diana; Palma, Vincenzo; Vaiano, Vincenzo; Mazzei, Roberto S.
Abstract : The performances of a gas-solid two-dimensional fluidized bed reactor in photocatalytic selective oxidation reactions, irradiated with traditional UV lamps or with a microscale illumination system based on UV emitting diodes (UVA-LEDs), have been compared. In the photocatalytic oxidative dehydrogenation of cyclohexane to benzene onMoO x / TiO 2 - A 1 2 O 3 catalyst the use of UVA-LEDs modules allowed to achieve a cyclohexane conversion and benzene yield higher than those obtained with traditional UV lamps. The better performances with UVA-LEDs are due to the UVA-LEDs small dimensions and small-angle emittance, which allow photons beam be directed towards the photoreactor windows, reducing the dispersion outside of photoreactor or the optical path length. As a consequence, the effectively illuminated mass of catalyst is greater. We have found that this illumination system is efficient for photo-oxidative dehydrogenation of cyclohexane to cyclohexene on sulphatedMoO x / γ - A 1 2 O 3 and ethanol to acetaldehyde onVO x / TiO 2 .